Rice Root Nematode an emerging threat to irrigated rice - Berliner, J; Pokhare, S Somnath; Adak, Totan; Guruprasannapandi, Guruprasannapandi (Indian Farming, 2017)
The RRN are the most frequent nematode species encountered in irrigated rice ecosystem, whose population yield may range from 100-600 nematode/100 CC soil. Though it is unseen and unable to cause visible symptoms, the distribution and abundance of the RRN urge the importance of systematic study to evaluate its economic loss, lifecycle (voltinism), pathogenic ability, adaptability and survival ability to prevent possible outbreaks.